Analisis faktor-faktor produksi pengusaha genteng di Desa Kendal Kecamatan Girimarto Kabupaten Wonogiri - Amalia, Alfida Nizar; Purnomo, Didit (Nur Science Institute, 2024)
This research aims to determine and analyze the raw materials, labor, fuel and length of business for roof tile production in Kendal village, Girimarto subdistrict, Wonogiri district. This research was conducted in Kendal village, Girimarto subdistrict, Wonogiri district, with 56 roof tile entrepreneurs as respondents. Data was collected using a survey method in the form of primary and secondary data. Primary data was obtained by distributing questionnaires to roof tile entrepreneur respondents. Meanwhile, secondary data was obtained from articles, scientific journals, research theses, and village offices. Data analysis techniques use multiple linear regression and classical assumption tests. The research results show that raw materials and fuel significantly affect roof tile production in Kendal village, Girimarto subdistrict, Wonogiri district. Meanwhile, labor and business length do not significantly affect roof tile production in Kendal village, Girimarto subdistrict, Wonogiri district. The results of the scale of roof tile production in Kendal village, Girimarto subdistrict, Wonogiri district show decreasing returns to scale, which means that every additional production factor input will produce a smaller proportion of production output.